Intransitive Verb Markers in Balinese - I Gede Bagus Wisnu Bayu Temaja (Masyarakat Linguistik Indonesia Universitas Andalas, 2018)
This research investigated intransitive verb markers in Balinese. The objectives of the research were: 1) to identify various markers of intransitive verb construction, and 2) to identify the syntactic behaviours of the markers in marking the intransitive verb. The research was conducted in three stages: data collection, data analysis, and data display. The data were collected by applying interview method. The data were obtained from Balinese speakers, Balinese literature, as well as the researcher as a native speaker of Balinese. The data were analyzed by using the distributional method. The display of the results were done formally and informally. The results show that there are four intransitive verb markers consist of ma-, N- (ny-, ng-, and m-), ma-an, and ma-in markers. The occurrence of intransitive verb markers as in ma- and N- are located on the left of the verb while marker ma-an and ma-in are located on the left and right of the verb. The four markers categorize as bound morpheme and placed as a central marker. The marking direction of the entire markers is considered as markers of a central element that mark the verb itself in order to form intransitive verb construction.